Low-dose combined exposure of nanoparticles and heavy metal compared with PM2.5 in human myocardial AC16 cells - Feng, L.; Yang, X.; Asweto, Collins O.; Wu, Jing; Zhang, Y; Hu, H.; Shi, Y.; Duan, Junchao; Sun, Z. (Springer, 2017)
The co-exposure toxicity mechanism of ultrafine particles and pollutants on human cardiovascular system are still unclear. In this study, the combined effects of silica nanoparticles (SiNPs) and/or carbon black nanoparticles (CBNPs) with Pb(AC)2 compared with particulate matter (PM)2.5 were investigated in human myocardial cells (AC16). Our study detected three different combinations of SiNPs and Pb(AC)2, CBNPs and Pb(AC)2, and SiNPs and CBNPs compared with PM2.5 at low-dose exposure. Using PM2.5 as positive control, our results suggested that the combination of SiNPs and Pb(AC)2/CBNPs could increase the production of reactive oxygen species (ROS), lactate dehydrogenase leakage (LDH), and malondialdehyde (MDA) and decrease the activities of superoxide dismutase (SOD) and glutathione (GSH); induce inflammation by the upregulation of protein CRP and TNF-α, and apoptosis by the upregulation of protein caspase-3, caspase-9, and Bax while the downregulation of protein Bcl-2; and trigger G2/M phase arrest by the upregulation of protein Chk2 and downregulation of protein Cdc2 and cyclin B1. In addition, the combination of CBNPs and Pb(AC)2 induced a significant increase in MDA and reduced the activities of ROS, LDH, SOD, and GSH, with G1/S phase arrest via upregulation of Chk1 and downregulation of CDK6 and cyclin D1. Our data suggested that the additive interaction and synergistic interaction are the major interaction in co-exposure system, and PM2.5 could trigger more severe oxidative stress, G2/M arrest, and apoptosis than either co-exposure or single exposure.
Keywords: Silica nanoparticles; Carbon black nanoparticles; Pb(AC)2; Combined cardiovascular toxicity; Human myocardial cells